A comprehensive study of SQL : practice and implementation - Patni, Jagdish Chandra (Chapman & Hall/CRC Press, 2023)
"'A Comprehensive Study of SQL - Practice and Implementation' is designed as a textbook and provides a comprehensive approach to SQL (Structured Query Language), the standard programming language for defining, organizing, and exploring data in relational databases. It demonstrates how to leverage the two most vital tools for data query and analysis - SQL and Excel - to perform comprehensive data analysis without the need for a sophisticated and expensive data mining tool or application"--